The Effect of Financial Leverage, Operating Leverage and Current Ratio on Profitability at PT. Manunggal Persada Jakarta - Waluyo Jati (PINISI Discretion Review, 2019)
Funds can be obtained from company owners or from outside parties. The purpose of this study was to determine the effect of financial leverage, operating leverage and current ratio on profitability at PT. Manunggal Persada Jakarta. The method used in this research is descriptive with an associative approach, the sampling technique used is proportional random sampling using the census or saturated sampling method with a sample of 7 years of financial statements. The analysis tool uses classical assumption testing, regression testing, determination coefficient testing and hypothesis testing. The results of the study concluded that the regression coefficient value of Financial leverage of 0.005 was positive with a contribution of 19.3%. Hypothesis testing obtained a significance value of 0.324> 0.05. Regression coefficient value of Operating leverage of 0.001 is positive with a contribution of 16.5%. Hypothesis testing obtained a significance value of 0.368> 0.05. Current coefficient regression value of 0.158 is positive with a contribution of 31.9%. Hypothesis testing obtained a significance value of 0.187> 0.05. Obtained a regression equation Y = 0.110 + 0.009X1 + 0.001X2 + 0.177X3, the regression coefficient value of each positive independent variable with a correlation of 0.927 and a coefficient of determination of 85.8% while the remaining 14.2% is influenced by other factors. Hypothesis testing obtained by calculating Fcount> Ftable or (6.064> 4.120). Thus simultaneously there is a positive and significant effect between financial leverage, operating leverage and current ratio to rentability.